2018
DOI: 10.3389/fendo.2018.00211
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics in Type 2 Diabetes and Cancer

Abstract: Mitochondria are bioenergetic, biosynthetic, and signaling organelles that control various aspects of cellular and organism homeostasis. Quality control mechanisms are in place to ensure maximal mitochondrial function and metabolic homeostasis at the cellular level. Dysregulation of these pathways is a common theme in human disease. In this mini-review, we discuss how alterations of the mitochondrial network influences mitochondrial function, focusing on the molecular regulators of mitochondrial dynamics (orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 85 publications
3
30
1
2
Order By: Relevance
“…Previous studies have shown that high glucose increased the protein expression and phosphorylation of DRP1, thus further leading to the translocation from cytoplasmic to the mitochondrial and increase in mitochondrial fission [28]. Moreover, DRP1 inhibitor mdivi-1, silencing of DRP1 or mutant of phosphorylation site could inhibit mitochondrial fission and improve biochemical and histological features of diabetic complications [29,30]. In our study, we demonstrated that the diabetic condition induces mitochondrial fission and excessive ROS production in macrophages.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have shown that high glucose increased the protein expression and phosphorylation of DRP1, thus further leading to the translocation from cytoplasmic to the mitochondrial and increase in mitochondrial fission [28]. Moreover, DRP1 inhibitor mdivi-1, silencing of DRP1 or mutant of phosphorylation site could inhibit mitochondrial fission and improve biochemical and histological features of diabetic complications [29,30]. In our study, we demonstrated that the diabetic condition induces mitochondrial fission and excessive ROS production in macrophages.…”
Section: Discussionsupporting
confidence: 58%
“…However, the mitochondrion plays a pivotal role in many other biological processes, where it shows high variation in structure, proteomic composition and function differentiated in tissues and cell types. Hence the current great interest in mitochondria and disease, as confirmed by clinical literature 1,2,3 .…”
Section: Introductionmentioning
confidence: 91%
“…This polyubiquitinates proteins on the outer mitochondrial membrane and degrades the damaged mitochondria, and biogenesis replenishes mitochondrial mass ( 10 ). Defective mitochondrial dynamic has been implicated in many chronic diseases, including cancer and diabetes ( 11 ).…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%